Herbicide Resistance in Weeds and Crops - Pacanoski, Zvonko (IntechOpen, 2017)
Herbicides are the dominant technology and the most effective weed control tools ever developed that are used for the control of weeds that infest crops. Over the last several decades, in situations of intense herbicide usage, there have been many examples of the evolution of weed populations resistant to herbicides. Weed adaptations to management tactics, including biochemical mimicry in the form of evolved resistance to the herbicides used for weed control, have increased rapidly throughout agriculture and now threaten global food security. Nowadays, expended space of research activities remains to focus on the herbicide resistance to weeds and crops. The authors of Herbicide Resistance in Weeds and Crops cover various issues regarding the present relevant research.